Pengaruh Kepatuhan Syariah Terhadap Kinerja Maqashid Sharia Perfomance dengan Intellectual Capital Sebagai Variabel Moderasi - Ikbar Andriano; Bima Cinintya Pratama; Hadi Pramono; Rina Mudjiyanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The performance of Islamic banks should not be assessed solely through financial indicators but also through their ability to realize ethical values and public welfare as reflected in the Maqashid Shariah framework. However, empirical studies that komprehensif eously examine the role of Intellectual Capital and Sharia Compliance in explaining Maqashid Shariah Performance (MSP) remain limited. This study aims to analyze the influence of key components of Intellectual Capital and the level of Sharia Compliance on the variation of MSP in Indonesian Islamic commercial banks. Using panel data from 2013–2023, the research employs a quantitative approach based on secondary data extracted from annual reports of Islamic banks. The findings indicate that human capital efficiency and structural capital contribute significantly to the achievement of Maqashid, while capital employed and sharia compliance do not exhibit meaningful effects. The moderation analysis further reveals that only the interaction between sharia compliance and structural capital strengthens MSP. These results highlight that the realization of Maqashid relies more on internal systems, human resource competence, and organizational structure rather than solely on formal compliance practices. This study contributes to the development of maqashid-based performance evaluation and provides practical implications for Islamic banks to enhance governance and internalization of sharia values.